Motivation Analysis of Mothers with Complete Basic Immunization in Toddlers Age 3 at the Public Health Center "W" Mimika Timika Papua in 2020 - Intan Fazrin; Siti Ifah Nurhasanah (Journal of Health Science Community, 2023)
Immunization program is one of the main prevention methods to avoid infectious diseases. The problem in this study is the lack of complete basic immunization coverage in the Kamoro Jaya sub-district, Wania 2020 District. The purpose of this study was to analyze the motivation of mothers to complete basic immunization in toddlers. This type of research is a cross sectional study of analytic correlation. The account population was all 300 mothers from various local integrated healthcare center areas and the number of samples was several mothers totaling 100 respondents. The sampling technique was simple random sampling. The dependent variable is the mother’s motivation and the independent variable is the completeness of basic immunization. Collecting data used by consent forms and questionnaires. Data processing is used by editing, coding, scoring, data entry, data tabulation and is used by the chi square correlation test motivational results with a number 112.220 and the completeness results were 23,040. The results showed that out of 100 respondents at the "W’’ Health Center, most (83%) were not motivated by 83 respondents, and the majority (74%) completed immunization in infants, namely 74 respondents. Chi square test analysis is obtained p-value =0.001 < α=0.05 (p-value < α) which means H0 rejected and H1 accepted. It can be concluded that there is a relationship between motivational factors and the completeness of immunization in toddlers at the Public Health Center "W" Mimika Timika Papua in 2020. So it is recommended for health workers to pay attention to the motivation of toddler mothers.